Proposed Marketing Strategy to Increase Merchandise Sales - Arista Pratama, Vito; Ashari Nasution, Reza; Furinto, Asnan (Fakultas Ekonomi Universitas Gresik, 2023)
Indonesia's retail industry is crucial for the country's economy, and PT Sarinah, a State Owned Enterprise (SOE), is the only SOE operating in this sector. Founded in 1962, PT Sarinah underwent a transformation in 2020, estimated to cost around 700 billion Rupiah. To promote the revamped Sarinah and increase revenue, the management decided to create official merchandise, but sales did not reach the target. This research aims to provide a marketing strategy to increase Sarinah merchandise sales and store visits. The internal factors analyzed include the current state of PT Sarinah's STP and 4Ps marketing mix, as well as the VRIO framework. The external factors will be examined using Porter's Five Forces framework, competitor analysis, and customer analysis. The proposed STP will be developed using a SWOT analysis, focusing on internal conditions (strength and weaknesses) and external conditions (opportunity and threat). The research found that PT Sarinah has unidentified segmenting, targeting, and positioning of Sarinah merchandise, limited product categories, uncompetitive prices, lack of uniqueness, and limited online presence. To overcome these challenges, PT Sarinah should position Sarinah merchandise as an affordable Indonesian essential, diversify its product categories, emphasize brand equity, optimize the supply chain, offer promotional offers, maintain quality, improve online purchasing experience, open stores in high-traffic areas, enhance social media presence, hire influencers, and conduct various activations. Additionally, employee involvement, customer experience, operational efficiency, and relationship management strategies should be implemented. Finally, renovating the current merchandise store and creating meaningful packaging and product presentation will further enhance the company's success.